A Multiagent Geosimulation Approach for Intelligent Sensor Web Management. (7th November 2010) - Mekni, Mehdi; Graniero, Phil
Abstract : A Sensor Web (SW) consists of a large collection of small nodes providing collaborative and distributed sensing abilities in unpredictable environments. Nodes composing such an SW are characterized by resource restrictions, especially energy, processing power, and communication capacities. A sensor web can be thought of as a spatially and functionally distributed complex system evolving in and interacting with a geographic environment. So far, the majority of the currently deployed SWs has been mainly used for prototyping purposes. These SWs operate without considering a management scheme and do not take into account the geographic environment characteristics in which they are deployed. Multiagent Geosimulation (MAGS) is a recent modeling and simulation paradigm which provides a flexible approach that can be used to analyze complex systems such as SW in large-scale and complex georeferenced environments. In this paper, we propose to use an MAGS approach to support SW management. Moreover, we present Sensor-MAGS, a multiagent geosimulation system which manages sensor nodes using Informed Virtual Geographic Environments (IVGE). This system is applied in the context of a water resource monitoring project.